Analisis Struktur dan kinerja Industri Makanan dan Minuman di Indonesia 2006-2009 - , Hoerip Satyagraha ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Food and beverage industry is one of important industry for Indonesia. It can be shown from BPS data that this industry together with tobacco industry can contribute 7,7% based on constant price and 8,2% based current price to PDB on 2009. It is interesting to be analyzed especially related to the structure and performance since this industry become one of economy backbone for Indonesia and facing attack of incoming food and beverage from Cina, as the consequence of agreement between Cina and ASEAN (ACFTA). This thesis concerns to research the structure and performance of food and beverage industry on 2006-2009 by using framework Structure-Conduct-Performance (SCP). This research intends to examine what the structure and performance of food and beverage industry is. It also assesses the relationship between them. The structure is analyzed by using concentration ratio of 4 biggest companies (CR4), while the industry performance is analyzed based on contribution of added value and employee number toward total added value and employee number of manufacture industry in Indonesia. This parameter also assessed based on its productivity and achieved efficiency. To assess the relationship between its structure and performance, this thesis uses multiple regression method and analyzed using software program SPSS version 10. The data used is pooling data which comprise of time series and cross section data. Based on the research result, the structure of food and beverage industry in Indonesia on 2006-2009 (KBLI 5 digit, comprises of 59 industry groups) spreads on variety of structure. There are 12 groups categorized as full oligopoly, 14 groups as high concentrated oligopoly, 6 groups as high moderate concentrated oligopoly, 17 groups as low moderate concentrated oligopoly and 10 groups as not concentrated industries. This industry contributes 16,39% value added and 15,83% employee number of manufacture industry. The productivity per employee average is Rp. 688.835.014/employee, while the efficiency is 66%. In term of relationship between structure and performance, the research shows that there is relationship between industry entry barrier and its performance while the structure has no correlation to its performance.